Bit Allocation Scheme for Low-Delay H.264/AVC Rate Control - Jiang, M.; Ling, N. (2006 International Conference on Image Processing, 2006)
This paper presents an efficient rate control scheme for H.264/AVC video coding in low-delay environments. In our scheme, we propose a close-form solution to optimal bit allocation problem subject to constraints and we derive theoretically a mean absolute difference based (MAD-based) complexity measure. The complexity measure of the current macroblock is also used to predict SKIP mode such that the initial quantization parameter (QP) is determined directly. Initial QPs of other kind of macroblocks (MBs) are computed based on a conventional quadratic model. To prevent the buffer from undesirable overflow or underflow under small buffer size constraint, the obtained initial QP is further adjusted based on actual encoding results at that point. Simulation results show that the H.264 encoder, using our proposed scheme, achieves a visual quality improvement of about 0.65 dB on the average and performs better for buffer overflow and underflow.